Time series measurements from a lab-on-chip dissolved silica (DSi) sensor deployed in a glacier-fed fjord (Nuup Kangerlua, Greenland) between June and September 2019 - Alexander Beaton; Katharine R Hendry; Jade Elizabeth Hatton; Lorenz Meire (PANGAEA, 2025)
This is a time-series record dissolved silica (DSi) collected using an in situ lab-on-chip sensor that was deployed in a glacier-fed fjord (Nuup Kangerlua) between 14th June to 13th September 2019. The sensor (along with a conductivity, temperature and depth (CTD) probe) was attached to a frame that was anchored to a cliff and submerged at an average depth of 5 m. The sensor was programmed to draw in ambient water (through 0.45 μm pore-size 13 mm diameter polyethersulfone inlet filter) and measure its DSi concentration every 12 hours. Each measurement was accompanied by the measurement of an onboard calibration standard and a blank solution (artificial seawater). During a three-month monitoring period DSi varied between 0.35 and 14.98 μM (± 0.5 μM).